2021
DOI: 10.3390/polym13071154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a PCL-3D Printing-Dental Pulp Stem Cells Triplet for Bone Engineering: An In Vitro Study

Abstract: The search of suitable combinations of stem cells, biomaterials and scaffolds manufacturing methods have become a major focus of research for bone engineering. The aim of this study was to test the potential of dental pulp stem cells to attach, proliferate, mineralize and differentiate on 3D printed polycaprolactone (PCL) scaffolds. A 100% pure Mw: 84,500 ± 1000 PCL was selected. 5 × 10 × 5 mm3 parallelepiped scaffolds were designed as a wood-pilled structure composed of 20 layers of 250 μm in height, in a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…According to these results, samples were washed using deionized water at a boiling temperature under mechanical stirring and adding to the rest of the solution during 2 to 3 min, and finally filtered to get the samples to be dried. The washing process was completed twice, and again pH was measured until values of 6.9 for JKCa, 7.2 for JKCa2 and 7.4 for JKAll were obtained, which are acceptable to be used in cell assays [30].…”
Section: Synthesis Of the Doped Potassium Jarositementioning
confidence: 99%
See 1 more Smart Citation
“…According to these results, samples were washed using deionized water at a boiling temperature under mechanical stirring and adding to the rest of the solution during 2 to 3 min, and finally filtered to get the samples to be dried. The washing process was completed twice, and again pH was measured until values of 6.9 for JKCa, 7.2 for JKCa2 and 7.4 for JKAll were obtained, which are acceptable to be used in cell assays [30].…”
Section: Synthesis Of the Doped Potassium Jarositementioning
confidence: 99%
“…Alizarin red staining can be used as an indicator of osteogenic differentiation [30]. After seeding the swine dental pulp stem cells in a 24-well plate, 10 mm 3 of jarosite powder (group b, c and e) was added.…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
“…Poly(ε-caprolactone) (PCL) is a suitable synthetic polymer for use in bone tissue engineering because of its mechanical strength, thermoelastic behavior, adjustment of structural degradation time in proportion to recovery biocompatibility, and rapid freezing due to its calcium ions. However, PCL shows low performance, low flexibility, and lack of cell attachment sites, and there are no functional groups in the polymer chain compared with the natural bone tissue 9 , 15 17 . PCL easily combines with other synthetic and natural polymers and bioceramic materials to allow PCL properties to be precisely adjusted 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hydroxyapatite (HA) is the most stable form of calcium phosphate at the body’s pH. Moreover, it is very suitable for bone substitute due to its excellent osteoconductivity, biocompatibility, cell binding, and proliferation 15 17 . Numerous experiments have been conducted using PCL and HA materials in combined biomedical scaffolds for bone tissue engineering applications 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the morphology can be controlled using this technique, while cell viability tests and staining with von Kossa red and Aliazarin showed the binding, proliferation and differentiation capacity levels of swine dental pulp stem cells (DPSCs) in the obtained PCL scaffolds. These results indicate that these biomaterials have potential uses in additional models and preclinical experiments for bone engineering studies [ 36 ].…”
Section: Biomaterials Applied In Bone Regenerationmentioning
confidence: 99%